1998
DOI: 10.1038/sj.bmt.1701153
|View full text |Cite
|
Sign up to set email alerts
|

The effect of T cell depletion with Campath-1M on immune reconstitution after chemotherapy and allogeneic bone marrow transplant as treatment for leukaemia

Abstract: The prophylactic use of T cell depletion (TCD) strategies for the prevention of graft-versus-host disease (GVHD) following allogeneic stem cell transplantation remains widespread. Initial reports of high incidence of graft rejection after TCD BMT led to a move away from this approach but improved conditioning regimens have reduced this risk substantially. The use of TCD has also been associated with higher relapse risk post-BMT although the success of donor leukocyte infusion (DLI) as treatment for relapse has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
29
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 21 publications
(23 reference statements)
5
29
0
Order By: Relevance
“…5,8 Phenotypic analysis of PBMC demonstrated that within 3-6 months various cell subpopulations recover and most return to normal levels within 12 months post allogeneic transplantation. 6,22,[25][26][27] Following both myeloablative and low intensity conditioning, our FACS analysis of PBMC is in accordance with data published previously, showing a decrease in the absolute number of CD4 + cells accompanied by an increase in CD8 + cells which led to an inverted CD4/CD8 cell ratio. 6,22,[25][26][27] Both regimens resulted in a long-lasting increase in activated cells carrying the HLA-DR cell surface marker in contrast to the number of HLA-DR + cells in normal PBMC.…”
Section: Discussionsupporting
confidence: 79%
“…5,8 Phenotypic analysis of PBMC demonstrated that within 3-6 months various cell subpopulations recover and most return to normal levels within 12 months post allogeneic transplantation. 6,22,[25][26][27] Following both myeloablative and low intensity conditioning, our FACS analysis of PBMC is in accordance with data published previously, showing a decrease in the absolute number of CD4 + cells accompanied by an increase in CD8 + cells which led to an inverted CD4/CD8 cell ratio. 6,22,[25][26][27] Both regimens resulted in a long-lasting increase in activated cells carrying the HLA-DR cell surface marker in contrast to the number of HLA-DR + cells in normal PBMC.…”
Section: Discussionsupporting
confidence: 79%
“…20 We also expect enhanced immune reconstitution since this has been shown to be directly proportional to the number of T cells in the infused graft. 8 This method may also exploit antigen differences on normal tissues and leukaemia cells in that donor responses to recipient MHC and ubiquitous mHA are eliminated while conserving responses to lineage-restricted or even leukaemia-specific antigens. This would translate into a graft-mediated antileukaemia activity.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] So far, successful use of T cell depletion has required the establishment of an appropriate balance between the residual immune response of the recipient, which can be achieved by enhanced conditioning, and the adjustment of the T cell content of the donor bone marrow. 8,9 That T cells play an integral role in the mechanisms of graft rejection, GVHD and in GVL activity is no longer in doubt. What has proved to be more difficult has been the identification of specific subsets of cells involved in each of these activities.…”
mentioning
confidence: 99%
“…5 At the time we started the study, NK alloreactivity started to emerge as a major player in the GVL effect of the transplant, 6 which was confirmed later on 4 and we have incorporated these data from the start in choosing the donor. Since T-celldepleted transplants are 'per se' at a higher risk of relapse, 7 we thought that the other parameters upon which to play were T cell add-back and the type of growth factors used post-transplant.…”
mentioning
confidence: 99%